Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1651-2227.2008.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Total serum bilirubin levels during cyclooxygenase inhibitor treatment for patent ductus arteriosus in preterm infants

Abstract: In VLBW infants with PDA, ibuprofen treatment was associated with higher bilirubin levels than indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 20 publications
(26 reference statements)
1
18
1
Order By: Relevance
“…In addition, two in vivo studies have demonstrated that ibuprofen treatment results in higher peak levels of total serum bilirubin and longer durations of phototherapy. [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two in vivo studies have demonstrated that ibuprofen treatment results in higher peak levels of total serum bilirubin and longer durations of phototherapy. [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Ibuprofen is thought to impair biliary excretion of bilirubin and therefore it raises serum bilirubin level. 41,42 In addition, at higher serum concentration ibuprofen can displace bilirubin from its binding to albumin. 38 Indeed, a recent study showed that ibuprofen augments bilirubin toxicity in rat cortical neuronal culture.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TB levels also tended to fall on consecutive postnatal days when TB levels would have been expected to rise as a result of the normal development of the physiologic neonatal hyperbilirubinemia (27), indicating that more bilirubin could have been shifted from plasma into the tissue space during treatment with ibuprofen. On the other hand, in two recent clinical studies, ibuprofen has been shown to slightly but significantly increase TB in infants with PDA (28,29). However, UB concentrations were not measured in these studies.…”
Section: Discussionmentioning
confidence: 59%
“…However, UB concentrations were not measured in these studies. In the study by Rheinlaender et al (28), infants treated with ibuprofen were compared with infants treated with indomethacin. Although neurodevelopmental outcome at 2 y of age did not differ between the groups, single case analysis identified four cases of adverse neurodevelopmental outcome in the ibuprofen group despite inconspicuous clinical course.…”
Section: Discussionmentioning
confidence: 99%